Synthesis and Studies of Antibacterial Agents - Singh, C.P.; Nayal, S.S.; Chauhan, S.M. (Asian Journal of Chemistry, 2010)
A new series of hterocyclic compounds namely N1-(2-fluorobenzoyl)-5,5´-dimethyl cyclohexane 4-(sulpha/substituted phenyl azo)-1,2-diazoles have been synthesized and screened for their biological activity.